Analysis of legislative acts, regulating transportation of cargo in intermodal traffi c in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
The article is devoted to the analysis of legislative acts of the Republic of Kazakhstan, regulating transportation ofcargo in intermodal traffi c various modes of transport. Particular attention is paid to the relationship of the transportorganizations of different modes of transport for the transfer of cargo from one mode to another, the transfer points.In particular, the procedure of concluding nodal agreement transport organizations of different types of transport. Thearticle also covers issues pertaining to liability of participants direct multimodal transport. Author recommendations onharmonization of the legislative acts devoted to the specifi ed kind of transportations.Key words: transport; transportation of cargoes; direct intermodal transport; the contract of carriage of goods.